Effect of magnesium on the cardiovascular system in women - E. A. Ulubieva; A. G. Avtandilov (Рациональная фармакотерапия в кардиологии)
Recent scientific data on the influence of magnesium on the cardiovascular and reproductive system in women is summarized. Evidence-based medicine data has shown a link between magnesium blood (plasma, red blood cells) levels and increased risk of somatic diseases in women of reproductive age. Hypomagnesemia increases the risk of sudden cardiac death, unstable angina, and cardiovascular mortality due to myocardial tissue functional disorders, mitochondrial failure. Magnesium ions are essential for maintaining the physiological pregnancy. Experimental and clinical data allows using drugs of magnesium in preventing and treating heart disease in women. Their use is also possible for treatment of gynecological diseases, for pregnant women with arterial hypertension and connective tissue dysplasia.